2007
DOI: 10.1111/j.1466-7657.2007.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of, and attitudes to, acquired immune deficiency syndrome (AIDS) among traditional birth attendants (TBAs) in rural communities in Cross River State, Nigeria

Abstract: This survey has demonstrated that few TBAs in the communities studied in Cross River State are informed about HIV/AIDS, and this has revealed the urgency of starting a programme specifically designed for TBAs in rural communities towards a massive educational campaign on HIV/AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
(9 reference statements)
3
14
2
Order By: Relevance
“…The females in this study had better knowledge than the males and this was found to be statistically significant (p = 0.014). This was in contrast to the findings among TBAs in Cross Rivers state where the males (73.7%) had better knowledge of HIV than the females (28.9%) [19].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The females in this study had better knowledge than the males and this was found to be statistically significant (p = 0.014). This was in contrast to the findings among TBAs in Cross Rivers state where the males (73.7%) had better knowledge of HIV than the females (28.9%) [19].…”
Section: Discussioncontrasting
confidence: 94%
“…These deficiencies were in consonance with results found from other TBAs studied in Nigeria. [5,12,19,20] Some of the respondents also mentioned the use of agbo, a local concoction which they drunk regularly and gave to pregnant women as a way to protect against HIV. The unscientific practices by the TBAs can encourage the spread of HIV by giving a false impression of being protected and therefore not employing more valid means of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Because relatively few births occur within the health care system in Nigeria, HBI could be used to distribute infant ARV prophylaxis by working with traditional birth attendants in the communities. 39 Studies have found that with training, traditional birth attendants are able to administer ART peripartum, enhancing PMTCT. 40 Few intervention studies have targeted critical steps for PMTCT further down the continuum of care, and IS research is needed to improve EID uptake, ARV prophylaxis for exposed newborns, and linkage to care for HIV-infected infants.…”
Section: Discussionmentioning
confidence: 99%
“…Other access related issues include high user-fees, limited health facilities within reasonable commuting distance, and poor HW attitudes, including their lack of respect in care-giving. Furthermore, the fear of stigma and loss of privacy were additional reasons many pregnant women living with HIV/AIDS (PLWHAs) do not use skilled birth attendance in Nigeria [31], [32], [33], [34].…”
Section: Introductionmentioning
confidence: 99%